If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=-2/3+15
We move all terms to the left:
y-(-2/3+15)=0
We get rid of parentheses
y-15+2/3=0
We multiply all the terms by the denominator
y*3+2-15*3=0
We add all the numbers together, and all the variables
y*3-43=0
Wy multiply elements
3y-43=0
We move all terms containing y to the left, all other terms to the right
3y=43
y=43/3
y=14+1/3
| 2x+72=7x-8. | | 9x+2=12x-37 | | 4x=621 | | a=1000(1+(0.06)(0)) | | x+1/7=1/3 | | x/150=0.8 | | (x)=-15 | | 4x-8=-4(x+3) | | 4x-23+2x+11=180 | | 3x=@= | | a=1000(1+(0.06)(1)) | | 2x-23=2x+11 | | 10.2+x/7=-7.3 | | c/2.8=13.7 | | 37.2+x=93.89 | | a=1000(1+(0.06)(2)) | | 5m+9=37 | | 2(x-12)+6=-4(x+3) | | -9.5=-3.1+w/4 | | 3x+11=-4-2x | | (10x+7)=88 | | 2,1–0,3y=0,4y | | -9.5=-3.1w/4 | | y=(-3)+9 | | 4(2x+2.50)=31.50 | | (2d-7)=-5 | | y=(-6)+9 | | 4x+5+2x=6x-3 | | (-a+2)-9=6 | | -12=4m+4 | | w–15=–22 | | -3w+16+10w=-26 |